Device nurse intervention facilitates the patients' adaptation to cardiac shock devices in the remote monitoring era. Issue 11 (9th September 2021) - Ogawa, Tomomi; Saito, Nao; Fukuzawa, Koji; Kiuchi, Kunihiko; Takami, Mitsuru; Hayashi, Megumi; Tanioka, Ryo; Ota, Masaya; Komoriya, Keizo; Miyawaki, Ikuko; Hirata, Ken‐ichi
Abstract: Background: A s ubstantial number of patients with shock devices (implantable cardioverter defibrillators [ICDs] or ICDs with resynchronization [CRTDs]) experience psychological distress. Objective: We investigated the device nurse telephone intervention's effect on improving the patient's adaptation to shock devices, quality of life (QOL), and anxiety in the remote monitoring era. Methods: The patient's adaptation to the device, health‐related QOL, and anxiety were investigated by the modified Implanted Devices Adjustment‐Japan score (IDAS), Short Form‐36, and State‐Trait Anxiety Inventory (STAI) before and 1‐year after the device nurse telephone intervention, performed every 3 months. A total of 95 patients (median age 69 years and 25 females) participated. Sixty patients had ICDs and 35 CRTDs. Structural heart disease was observed in 72 patients, and idiopathic ventricular arrhythmias in the others. The mean left ventricular ejection fraction was 46% ± 15%. The median duration since the device implantation was 5.2 years. Results: The total IDAS score significantly improved from 28.42 ± 7.11 at baseline to 26.77 ± 7.68 ( p = 0.0076) at 1 year. Both the state and trait anxiety significantly improved (from 38.9 ± 9.6 to 35.3 ± 9.0 [<0.0001] and 38.8 ± 10.3 to 36.2±9.8 [ p = 0.0044], respectively). The prevalence of patients with a state and trait anxiety of more than 40 decreased from 44 (46%) and 38 (40%) patients before the study to 27 (28 %) and 32 (34 %) at 1 year. The SF‐36 mental component summary score significantly increased (50.8 ± 8.3 at baseline to 53.1 ± 7.7 at 1 year, p = 0.0031). Conclusions: The device nurse intervention facilitated the patient's adaptation to the shock device, increased the health‐related QOL, and reduced the patient's anxiety.